Increase in beaver dams controls surface water and thermokarst dynamics in an Arctic tundra region, Baldwin Peninsula, northwestern Alaska. (30th June 2020) - Jones, Benjamin M; Tape, Ken D; Clark, Jason A; Nitze, Ingmar; Grosse, Guido; Disbrow, Jeff
Abstract: Beavers are starting to colonize low arctic tundra regions in Alaska and Canada, which has implications for surface water changes and ice-rich permafrost degradation. In this study, we assessed the spatial and temporal dynamics of beaver dam building in relation to surface water dynamics and thermokarst landforms using sub-meter resolution satellite imagery acquired between 2002 and 2019 for two tundra areas in northwestern Alaska. In a 100 km 2 study area near Kotzebue, the number of dams increased markedly from 2 to 98 between 2002 and 2019. In a 430 km 2 study area encompassing the entire northern Baldwin Peninsula, the number of dams increased from 94 to 409 between 2010 and 2019, indicating a regional trend. Correlating data on beaver dam numbers with surface water area mapped for 12 individual years between 2002 and 2019 for the Kotzebue study area showed a significant positive correlation (R 2 = 0.61; p < .003). Beaver-influenced waterbodies accounted for two-thirds of the 8.3% increase in total surface water area in the Kotzebue study area during the 17 year period. Beavers specifically targeted thermokarst landforms in their dam building activities. Flooding of drained thermokarst lake basins accounted for 68% of beaver-influenced surface water increases, damming of lake outlets accounted for 26%, and damming of beaded streams accounted for 6%. Surface water increases resulting from beaver dam building likely exacerbated permafrost degradation in the region, but dam failure also factored into the drainage of several thermokarst lakes in the northern Baldwin Peninsula study region, which could promote local permafrost aggradation in freshly exposed lake sediments. Our findings highlight that beaver-driven ecosystem engineering must be carefully considered when accounting for changes occurring in some permafrost regions, and in particular, regional surface water dynamics in low Arctic and Boreal landscapes.